2003
DOI: 10.1093/jn/133.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Feed Restriction Significantly Alters Lipogenic Gene Expression in Broiler Breeder Chickens

Abstract: Broiler breeder pullets were divided into two groups at 21 wk of age. One group was given free access to feed (ad libitum) and the other fed a limited amount of feed (restricted). At 22 wk, all birds were photostimulated and maintained throughout an egg-laying cycle ending at 36 wk. Samples of liver and abdominal fat pad were collected just before photostimulation (prelight), after photostimulation at first egg and at peak egg production (plateau). Hepatic expression of sterol regulatory element binding protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
5
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 32 publications
7
74
5
6
Order By: Relevance
“…Moreover, the changes in protein levels of PPARg, FAS and ATGL were basically consistent with the changes in mRNA expression. It has been found that changes in feed intake had significant effects on genes expression in the animal for a long time (Richards et al, 2003;Sun et al, 2006). However, NDV infection has more quick and severe changes on gene expression in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…Moreover, the changes in protein levels of PPARg, FAS and ATGL were basically consistent with the changes in mRNA expression. It has been found that changes in feed intake had significant effects on genes expression in the animal for a long time (Richards et al, 2003;Sun et al, 2006). However, NDV infection has more quick and severe changes on gene expression in our study.…”
Section: Discussioncontrasting
confidence: 55%
“…In birds, lipogenesis (the conversion of glucose to TGs) takes place primarily in the liver, whereas the adipocyte serves as the storage site for TGs (Cogburn et al, 2004). Hepatic lipogenesis plays a direct role in the accumulation of lipid in the avian adipocyte, and 80% to 85% of the FAs stored in adipose tissue are generated through lipogenesis in the liver or from the diet (Richards et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fat tissues, glucose and other nutrients are converted into fatty acids by the FASregulated pathway (Richards et al, 2003). Therefore, overexpression of FAS would increase triglyceride deposition in the body, which may cause obesity (Richards et al, 2003;Matsubara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%